A schedule for phasing-out knife crime - Graham Farrell; Toby Davies (Crime Science)
Abstract Knife crime has become a prominent and seemingly intractable problem in England & Wales. Theory and evidence indicate that reducing crime opportunities is an effective means of crime control, including restrictions on lethal weapons. While public debate has centred on zombie and other ‘status’ knives, the most prevalent homicide weapon is a kitchen knife. Here we argue that replacing lethal pointed-tip kitchen knives with safer round-tip knives would reduce knife crime with little or no displacement. Drawing on the approach to remove fossil-fuel vehicles from roads, we propose a phased removal of lethal kitchen knives that we estimate will cut knife-related homicide in half, reduce other knife crime and criminality, and prevent thousands of non-criminal knife-related injuries.